Peningkatan Efisiensi Administrasi Human Capital Melalui Manajemen Kebutuhan Karyawan di PLN Nusantara Power Services Sidoarjo - Kamal, Favian Almer; Dwiridotjahjono, Jojok (Ikatan Da'i Indonesia, 2024)
This study discusses the improvement of human capital administration efficiency through employee needs management at PLN Nusantara Power Services Sidoarjo. The purpose of this internship is to provide valuable practical experience, as well as help participants develop relevant skills for future careers. The research methods used include questionnaires, employee surveys, interviews, and analysis and analysis of performance reports to understand the skills needed and potential gaps in the current workforce. The results show that the implementation of a human resources information system (HRIS) and the improvement of the recruitment and selection process have proven effective in reducing administrative burdens and increasing data accuracy. The use of HRIS has facilitated the management of employee data, payroll, and absence management, leading to higher operational efficiency. The study concludes that steps taken in employee development, performance management, and compensation and benefits policies also play an important role in improving human capital efficiency. Continuous training programs and systematic performance appraisals support employee professional growth and increase job satisfaction.